Gender in the Integration of Batik Ethnomathematics and Fiqh: Learning Models, Numeracy, and Trustworthiness - Agus Miftakus Surur; Muhammad Za’im An-Naufal; Pandi Rais; M. Ubaidillah Ridwanulloh Ridwanulloh; Sri Pujilestari; Cecep Soleh Kurniawan (Center for Gender and Child Studies, Institute for Research and Community Service, Institut Agama Islam Negeri Parepare., 2025)
Mathematics education in Indonesia continues to face challenges in developing students’ numeracy literacy, partly due to the limited integration of cultural, Islamic, and gender perspectives in pedagogical practices. This study seeks to design and validate an integrative learning model that merges batik ethnomathematics, Islamic jurisprudence (fiqh) values, and gender inclusivity to enhance students’ numeracy literacy and trustworthiness (amanah). A quasi-experimental method employing a pretest–posttest non-equivalent control group design was applied. The experimental class received instruction based on batik ethnomathematics integrated with fiqh values, while the control class followed a conventional approach. The findings demonstrate that embedding geometric concepts within batik ethnomathematics made learning more contextual, meaningful, and culturally relevant. The inclusion of fiqh principles, such as amanah and fairness, fostered students’ Islamic character development, while gender-responsive strategies promoted equitable participation among male and female learners. This study extends existing ethnomathematics scholarship by proposing a cohesive instructional framework that bridges cultural, ethical, and pedagogical dimensions. Theoretically, it enriches the discourse on numeracy literacy through the synthesis of ethnomathematics and Islamic moral education. Practically, it offers a model for implementing gender-responsive and value-based mathematics learning that cultivates trustworthiness and inclusivity in diverse educational contexts.